PM.88 Sepsis – Keeping an Open Mind!. (26th April 2013) - Vanes, NK; Holding, G; Jeevan, D; Mukherjee, S
Abstract : We present an unusual case of sepsis in a 23 year old lady of 14 weeks gestation (para 1 + 1) who presented with epigatric pain. Initial presentation was with bilious vomiting which became blood stained. She reported not opening bowels for 2 days however had passed flatus. There was no significant past medical history with only appendicectomy performed 5 years previously. On examination abdomen was slightly distended with tenderness in the epigastric region. Bloods were: WCC 2.5, Neut 1.5. Other bloods including amylase were normal. She was reviewed by the surgical team 'biliary colic' and an abdominal ultrasound performed, was normal. She was reviewed by medical, surgical, obstetric and gastroenterology teams and finally the diagnosis was of hyperemesis gravidarum. She was readmitted 48 hours later with pyrexia, tachycardia and hypotension. An ultrasound was performed which demonstrated increased free fluid and an emergency laparotomy was performed. Findings were that of a perforated distal ileum. A resection of the ascending colon and terminal ileum was performed with an ileostomy. Unfortunately, 3 days post operatively she miscarried despite the fetal heart being present immediately post operatively. During recovery she admitted that her sister in law had contracted tuberculosis and she herself had not been vaccinated. Investigations for TB are currently ongoing. Intra-abdominal fluid samples have confirmed the presence of ESBL. Although an unusual presentation, this case highlights the importance of maintaining a high suspicion of sepsis. This is especially true where blood results suggest this, in the absence of other features and ongoing symptoms.